Staging reinterventions for remodeling of residual aortic dissection: a single-center retrospective study - Chen, Bailang; Huang, Kunpeng; Zhuang, Xianmian; Wang, Zanxin; Wei, Minxin (Frontiers in Cardiovascular Medicine, 2024)
Abstract Objective: Inadequate remodeling of residual aortic dissection (RAD) following repair of Stanford A or B aortic dissections has been identified as a significant predictor of patient mortality. This study evaluates the short- to mid-term outcomes of staged reinterventions for RAD at a single center with prospective follow-up. Methods: Data were retrospectively collected from patients with RAD who underwent staged reinterventions or received none-surgery treatment in the Cardiovascular Surgery Department of our hospital between July 2019 and December 2021. The cohort included 54 patients with residual distal aortic dissection post-primary surgery, comprising 28 who underwent open surgery and 26 who received thoracic endovascular aortic repair (TEVAR). Patients were divided into two groups: those who underwent staged stent interventions for distal dissection (staged reintervention [SR] group) and those who did not undergo surgery (non-surgery group). For the SR group, second or third staged stent interventions were performed. The study assessed distal remodeling of aortic dissection between the groups, focusing on endpoints such as mortality (both general and aortic-specific), occurrences of visceral branch occlusion, necessity for further interventions, and significant adverse events. Morphological changes were analyzed to determine the therapeutic impact. Results: The study encompassed 54 participants, with 33 in the SR group and 21 in the non-surgical control group. Baseline demographics and clinical characteristics were statistically comparable across both groups. During an average follow-up of 31.5±7.0 months, aortic-related mortality was 0% in both groups; all-cause mortality was 3% (one case) and 5% (one case) in the SR and control groups, respectively, with no statistically significant difference noted. In the SR group, a single patient experienced complications, including renal artery thrombosis, leading to diminished blood flow. An increased true lumen (TL) area and a decreased false lumen area at various aortic planes were observed in the SR group compared to the control group. Conclusion: The staged reintervention strategy for treating RAD is safe and provides promising early results. Keywords: Staging reintervention; residual aortic dissection; aortic remodeling; entry tear; endovascular aortic repair